2018
DOI: 10.1038/s41598-018-31058-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Side Chain Polarity on Non-Stoichiometric Nano-Hydroxyapatite Surface Functionalization with Amino Acids

Abstract: In this study the affinity of three amino acids for the surface of non-stoichiometric hydroxyapatite nanoparticles (ns-nHA) was investigated under different reaction conditions. The amino acids investigated were chosen based on their differences in side chain polarity and potential impact on this surface affinity. While calcium pre-saturation of the calcium-deficient ns-nHA was not found to improve attachment of any of the amino acids studied, the polarity and fraction of ionized functional side groups was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…It is concluded that the amino acids predominantly bind to negatively charged P regions in consequence of the strong hydrogen bonds. However, it has been suggested that C sites can significantly increase or decrease the amino acid adsorption through electrostatic interactions [23][24][25][26]. In addition, it has been asserted that the side chains of the amino acids are highly effective in these binding preferences, hence the inhibition of the crystal growth [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…It is concluded that the amino acids predominantly bind to negatively charged P regions in consequence of the strong hydrogen bonds. However, it has been suggested that C sites can significantly increase or decrease the amino acid adsorption through electrostatic interactions [23][24][25][26]. In addition, it has been asserted that the side chains of the amino acids are highly effective in these binding preferences, hence the inhibition of the crystal growth [27][28][29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…All other reagents were purchased from Sigma-Aldrich Canada. We have previously reported on the characteristics of this nHA (Comeau and Willett, 2018). The nHA powder has been found to have a crystallinity of 66%, a Ca/P of 1.52 and is rod shaped with a ∼120 nm length and 20-30 nm width on average (Comeau and Willett, 2018).…”
Section: Methodsmentioning
confidence: 91%
“…The nHA powder has been found to have a crystallinity of 66%, a Ca/P of 1.52 and is rod shaped with a ∼120 nm length and 20-30 nm width on average (Comeau and Willett, 2018). In addition, ATR-FTIR spectroscopy of the raw native nHA has confirmed its carbonated nature (Comeau and Willett, 2018).…”
Section: Methodsmentioning
confidence: 95%
“…Chu et al39 revealed that Asp plays an important role in optimizing the efficacy of active sites (carboxylate-rich domains) and significantly decreases the interfacial energy barrier, inducing hydrated phase (HP) formation. However, a recent study by Patricia et al48 revealed that the interactions between ASP and hydroxyapatite are notably mediated by side chains, indicating that both the carboxyl and amine groups contribute significantly to the interaction. Whereas a high content of Asp residues may be effective for collagen binding,47 incorporation of Asp affects the degree of crystallinity of the apatitic phase, and the crystallinity decreases as the Asp content increases.…”
Section: Discussionmentioning
confidence: 99%
“…Asp is highly expressed in the small integrin-binding ligand, N-linked glycoproteins (SIBLINGs) protein family, and members of this family play important roles in hydroxyapatite mineralization in the body 47. Asp can be used as a crystal growth catalyst to modulate biomineralization effectively,40 and it controls hydroxyapatite mineralization in vivo 48…”
Section: Discussionmentioning
confidence: 99%